Trial as an Adult di Indonesia dan Implikasinya pada Hukum Pidana Serta Perlakuan Terhadap Anak-Anak Pelaku Tindak Pidana - Wirayudha Wibawa Hatma Syahputra (Ethics and Law Journal: Business and Notary, 2023)
Trial as an adult is a concept that allows the trial of children as adults in cases of serious crimes. The implications of this concept are related to the rights and protection of children, which are guaranteed by Article 28B paragraph 2 of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). This article explains that although there are no specific regulations regarding trials as adults in Indonesia, there are provisions in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) which provide opportunities for trials of children as adults in certain cases. However, trial as an adult in Indonesia raises various problems, both legally and in practice. This article states that legally, this concept is considered not in line with the principles of human rights and child protection, including the Convention on the Rights of the Child (KHA) and the 1945 Constitution of the Republic of Indonesia. It is also highlighted that trial as an adult is considered to violate the principles of legality and proportionality, because there is no clear definition of criminal offenses that can be the basis for trying children as adults. In the context of handling children involved in criminal acts, the SPPA Law emphasizes a restorative justice approach. This article highlights that this approach reflects the spirit of the Constitution, which focuses on children's rights and the principle of rehabilitation. However, the emergence of trial as an adult in some situations raises doubts about the consistency and fairness of the juvenile justice system. It is acknowledged that supporters of trial as an adult argue that children as perpetrators of criminal acts must be fully responsible, especially in serious cases. However, there are concerns that this approach could come at the expense of children's rehabilitation and rights. The article highlights that in practice, trial as an adult has a negative impact on children and society, including loss of children's rights, risk of violence, exploitation and discrimination in correctional institutions. In addition, trial as an adult is considered ineffective in preventing crime and reducing the risk of recidivism. This article summarizes the complexities of trials as an adult in Indonesia, showing the conflict between the need for justice, children's rights, and the effectiveness of the justice system. AbstrakTrial as an adult adalah konsep yang memungkinkan pengadilan anak sebagai orang dewasa dalam kasus tindak pidana serius. Implikasi konsep ini terkait dengan hak dan perlindungan anak, yang dijamin oleh Pasal 28B ayat 2 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD NRI 1945). Artikel ini menjelaskan bahwa meskipun belum ada regulasi khusus mengenai trial as an adult di Indonesia, terdapat ketentuan dalam Undang-Undang Nomor 11 Tahun 2012 tentang Sistem Peradilan Pidana Anak (UU SPPA) yang memberikan peluang bagi pengadilan anak sebagai orang dewasa dalam kasus tertentu. Namun, trial as an adult di Indonesia menimbulkan berbagai permasalahan, baik secara hukum maupun praktik. Artikel ini menyatakan bahwa secara hukum, konsep ini dianggap tidak selaras dengan prinsip-prinsip hak asasi manusia dan perlindungan anak, termasuk Konvensi Hak Anak (KHA) dan Konstitusi Republik Indonesia Tahun 1945. Disorot pula bahwa trial as an adult dianggap melanggar prinsip legalitas dan proporsionalitas, karena tidak ada definisi jelas mengenai tindak pidana yang dapat menjadi dasar pengadilan anak sebagai orang dewasa. Dalam konteks penanganan anak yang terlibat dalam tindak pidana, UU SPPA menonjolkan pendekatan keadilan restoratif. Artikel ini menyoroti bahwa pendekatan ini mencerminkan semangat Undang-Undang Dasar, yang berfokus pada hak anak dan prinsip rehabilitasi. Namun, munculnya trial as an adult dalam beberapa situasi menimbulkan keraguan akan konsistensi dan keadilan dalam sistem peradilan anak. Diakui bahwa pendukung trial as an adult berpendapat bahwa anak sebagai pelaku tindak pidana harus bertanggung jawab sepenuhnya, terutama dalam kasus serius. Meskipun demikian, ada keprihatinan bahwa pendekatan ini dapat mengorbankan rehabilitasi dan hak-hak anak. Artikel menyoroti bahwa dalam praktiknya, trial as an adult memberikan dampak negatif pada anak dan masyarakat, termasuk kehilangan hak-hak anak, risiko kekerasan, eksploitasi, dan diskriminasi di dalam lembaga pemasyarakatan. Selain itu, trial as an adult dianggap tidak efektif dalam mencegah kejahatan dan mengurangi risiko recidivism. Artikel ini merangkum kompleksitas trial as an adult di Indonesia, menunjukkan konflik antara kebutuhan keadilan, hak anak, dan efektivitas sistem peradilan.. Kata kunci: Trial as an Adult, Indonesia, Implikasi, Hukum Pidana, Perlakuan, Anak